The continuum of wood-induced channel bifurcations - Marshall, Anna; Wohl, Ellen (Frontiers in Water, 2023)
Accumulations of wood in rivers can alter three-dimensional connectivity and facilitate channel bifurcations. Bifurcations divide the flow of water and sediment into secondary channels and are a key component of anastomosing rivers. While past studies illustrate the basic scenarios in which bifurcations can occur in anastomosing rivers, understanding of the mechanisms of bifurcations remains limited. We evaluate wood-induced bifurcations across thirteen anastomosing reaches in nine different streams and rivers in the U.S. Rocky Mountains to address conditions that favor different bifurcation types. We hypothesize that (1) wood-induced bifurcations exist as a continuum of different patterns in anastomosing rivers and (2) the position of a river segment along this continuum correlates with the ratio of erosive force to erosional resistance (F/R). We use field data to quantify F/R and compare varying F/R to bifurcation types across sites. Our results support these hypotheses and suggest that bifurcation types exist as a continuum based on F/R. At higher values of F/R, more channel avulsion is occurring and predominantly lateral bifurcations form. At lower values of F/R, banks are more resistant to erosive forces and wood-induced bifurcations are transitional or longitudinal with limited lateral extent. The relationship between F/R and bifurcation types is not linear, but it is progressive. Given the geomorphic and ecological functions associated with large wood and wood-induced channel bifurcations, it becomes important to understand the conditions under which wood accumulations can facilitate different types of bifurcations and the processes involved in these bifurcations. This understanding can inform river corridor restoration designed to enhance the formation of secondary channels, increase lateral and vertical connectivity, and promote an anastomosing planform.